Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
[tex]e^x+3e^{-x}=4|\cdot e^x\\
(e^x)^2+3=4e^x\\
(e^x)^2-4e^x+3=0\\
(e^x)^2-e^x-3e^x+3=0\\
e^x(e^x-1)-3(e^x-1)=0\\
(e^x-3)(e^x-1)=0\\
e^x-3=0 \vee e^x-1=0\\
e^x=3 \vee e^x=1\\
x=\ln 3 \vee x=0
[/tex]
e^x+3e^-x=4
e^x+3/(e^x)=4
p=e^x
---------------------------
Continued...
p+3/p=4
p^2+3=4p
p^2-4p+3=0
(p-1)(p-3)=0
Therefore p=1 and p=3.
---------------------------
When p=1,
e^x=1
Therefore, x=ln1=0
-------------------------
When p=3,
e^x=3
Therefore x=ln3
e^x+3/(e^x)=4
p=e^x
---------------------------
Continued...
p+3/p=4
p^2+3=4p
p^2-4p+3=0
(p-1)(p-3)=0
Therefore p=1 and p=3.
---------------------------
When p=1,
e^x=1
Therefore, x=ln1=0
-------------------------
When p=3,
e^x=3
Therefore x=ln3
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.